Pengaruh Penghargaan Finansial, Pengakuan Profesional, Dan Pertimbangan Pasar Kerja Terhadap Pemilihan Karir Sebagai Konsultan Pajak Pada Mahasiswa Akuntansi - Wukir Diyah Prasetya; Banu Witono (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the influence of financial rewards, professional recognition, and job market considerations on accounting students' choice of career as a tax consultant. The data used in this research uses rpimer data with data collection techniques by distributing questionnaires via Google Form. The population of this study were all accounting students from universities in the city of Solo. There were 93 samples used by determining the sample using the incidental sample method. The results of this research indicate that financial rewards and job market considerations influence the choice of a career as a tax consultant for accounting students, while professional recognition does not influence the choice of a career as a tax consultant for accounting students. Keywords: Career Choice, Financial Rewards, Job Market Considerations, Professional Recognition